Teknik Penalaran Hukum: Deduktif, Induktif, dan Abduktif dalam Perspektif Penerapan Hukum - Tia Ludiana; Agi Attaubah Hidayat; Diding Jalaludin (Prodi Magister Ilmu Hukum Fakultas Hukum Universitas Singaperbangsa Karawang, 2025)
This paper aims to explore techniques in legal reasoning. The method used in this paper is a literature review. Various literature such as books, scientific articles, research results, case studies/notes and the like will be analysed to obtain a complete picture of legal reasoning techniques. Deductive reasoning is used to draw specific conclusions from general rules, inductive reasoning to draw general conclusions from specific facts, and abductive reasoning to construct hypotheses from incomplete facts. Each method has its own advantages and disadvantages, which contribute to the flexibility and adaptability of law in different situations. Deductive reasoning offers legal certainty, inductive reasoning allows for the development of new laws, and abductive reasoning helps to deal with uncertainty in legal investigation and interpretation.